2018
DOI: 10.1371/journal.pone.0200823
|View full text |Cite
|
Sign up to set email alerts
|

Early metabolic 18F-FDG PET/CT response of locally advanced squamous-cell carcinoma of head and neck to induction chemotherapy: A prospective pilot study

Abstract: ObjectiveThe objective of this study was to assess the clinical value of 18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) after the first cycle of induction chemotherapy (IC) in locally advanced squamous cell carcinoma of the head and neck (LASCCHN).Methods and findingsA prospective, single-arm, single center study was performed, with patients enrolled between February 2010 and July 2013.Patients (n = 49) with stage III/IVA–B LASCCHN who underwent IC with taxanes, cisplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…Until now, the major treatments for most patients with HNC include radiotherapy alone or in combination with chemotherapy, but local recurrence still remains the main reason for treatment failure in this group of patients. About 50% of patients have local recurrence after primary tumor resection, and despite active treatment, 25% of them develop distant metastases[1418]. Therefore, early diagnosis and precise prognosis of patients with HNC are critical and urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the major treatments for most patients with HNC include radiotherapy alone or in combination with chemotherapy, but local recurrence still remains the main reason for treatment failure in this group of patients. About 50% of patients have local recurrence after primary tumor resection, and despite active treatment, 25% of them develop distant metastases[1418]. Therefore, early diagnosis and precise prognosis of patients with HNC are critical and urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Desde las civilizaciones greco-romanas los Virus del Papiloma (VP) (36) se identificaron como causa de infección a través de la formación de verrugas; pero no fue hasta 1900 que la etiología de estas fue confirmada. A partir de ese momento, se identificaron VP en varias especies de vertebrados, incluyendo los humanos (37,38).…”
Section: Antecedentes Sobre El Virus Del Papiloma Humanounclassified
“…This has prompted interest in using FDG-PET/CT earlier during treatment to identify patients who may not respond. For example, a recent study suggested that FDG-PET/CT performed 14 days after the start of neo-adjuvant chemotherapy in patients with locally advanced disease was able to identify patients with poor outcomes, based on an increase in regional lymph node maximum SUV and insufficient decrease in primary tumor uptake after 2 weeks of treatment ( 47 ). Currently, the PERCIST thresholds (decrease ≥30%) do not vary according to the number of treatment cycles received (i.e., mid-treatment or end-of-treatment), which may change in subsequent versions ( 48 ).…”
Section: Quality Assurance and Control Of Fdg-pet/ctmentioning
confidence: 99%